1985
DOI: 10.1007/bf00431679
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminomimetic action of diphenylhydantoin in rat striatum: Effect on homovanillic acid and cyclic AMP levels

Abstract: Diphenylhydantoin (DPH) is known to induce reversible paroxysmal dyskinesias and paranoid psychosis in humans, but its interactions with dopamine (DA) metabolism are not clear. Single doses of DPH (60-100 mg kg-1), with serum levels over 10 micrograms ml-1, reduced homovanillic acid (HVA) levels in rat striatum. The DPH-induced HVA decrease was enhanced by supersensitivity of postsynaptic DA receptors following chronic haloperidol (Hal) administration. DPH 60 mg kg-1 given acutely enhanced the HVA decrease ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1987
1987
1998
1998

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Carbamazepine has a presynaptic dopaminereleasing action, both in vitro (Barros et al, 1986) and in vivo (Kaneko et al, 1993), which may well be a component of its anticonvulsant mechanism. Phenytoin leads to dopaminergic supersensitivity after long-term administration to rats (Lalonde, 1985; but see Lepore et al, 1985) and to dopamine-like orofacial dyskinesias in epileptic patients. Likewise, vigabatrin treatment of epilepsy has been sporadically linked to psychosis, with evidence of increased HVA levels in the CSF following acute (Ben-Menachem et al, 1989) but not chronic (Riekkinen et al, 1989) vigabatrin treatment and of increased *231-IBZM binding to Dz receptors in the basal ganglia of the left hemisphere of six chronic epileptics (Ring et al, 1992).…”
Section: Effects Of Chemoconvulsantsmentioning
confidence: 99%
“…Carbamazepine has a presynaptic dopaminereleasing action, both in vitro (Barros et al, 1986) and in vivo (Kaneko et al, 1993), which may well be a component of its anticonvulsant mechanism. Phenytoin leads to dopaminergic supersensitivity after long-term administration to rats (Lalonde, 1985; but see Lepore et al, 1985) and to dopamine-like orofacial dyskinesias in epileptic patients. Likewise, vigabatrin treatment of epilepsy has been sporadically linked to psychosis, with evidence of increased HVA levels in the CSF following acute (Ben-Menachem et al, 1989) but not chronic (Riekkinen et al, 1989) vigabatrin treatment and of increased *231-IBZM binding to Dz receptors in the basal ganglia of the left hemisphere of six chronic epileptics (Ring et al, 1992).…”
Section: Effects Of Chemoconvulsantsmentioning
confidence: 99%
“…creasing, if any, effect on DA turnover. Although some authors (Lepore et al, 1985) reported a dopaminomimetic action of phenytoin and a subsensitivity of DA receptors after chronic administration of the drug, others (Lalonde, 1985) proposed a dopaminergic supersensitivity as a result of a long-term phenytoin administration.…”
mentioning
confidence: 99%